Simplicial homeomorphs and trace-bounded hypergraphs - Jason Long; Bhargav Narayanan; Corrine Yap (Discrete Analysis)
Simplicial homeomorphs and trace-bounded hypergraphs, Discrete Analysis 2022:6, 12 pp.